Analysis of lighting in virtual learning environments in students of the Private University of Tacna during confinement by COVID-19 - Vera Mazuelos, Gabriela Alexandra (2021)
The research was carried out with the purpose of determining whether the study environment used by the students of the Private University of Tacna during the confinement by COVID-19, complies with the light requirements necessary to guarantee a healthy space, considering the regulations and indexes lighting standards. The methodology was framed within the type of applied research, whose study population was the student body of the Private University of Tacna with a sample of 222 students to whom a survey of 20 questions was applied. The method of light analysis of study environments in relation to compliance with the technical standard EM.010 Indoor electrical installations of the National Building Regulations (annex: minimum lighting requirements) was carried out in 7 homes; using an Extech model 407026 lux meter. The results found indicate that the recommended rates of 500lx are not reached at any time of the day and that the rates found in the study environments are below what is established. It is concluded that in all cases it is necessary to add a luminaire with lighting directed to the work plane with conditions close to 1800 lumens, 6500K and 18w.